Triple-Negative Breast Cancer: Intact Mismatch Repair and Partial Co-Expression of PD-L1 and LAG-3 - Wu, Shafei; Shi, Xiaohua; Wang, Jing; Wang, Xuefei; Liu, Yuanyuan; Luo, Yufeng; Mao, Feng; Zeng, Xuan (Frontiers in Immunology, 2021)
Background and Aim Poor response to immune checkpoint inhibitors (ICIs) has been observed in most triple-negative breast cancer (TNBC) cases (around 80%). Our aim was to investigate the status of mismatch repair (MMR), microsatellite instability (MSI), programmed death-ligand 1 (PD-L1), and lymphocyte-activation gene 3 (LAG-3) in TNBC. Methods A total of 74 TNBC samples were retrospectively analyzed. MMR and MSI were evaluated by immunohistochemistry (IHC) and polymerase chain reaction (PCR) using Promega 1.2 and NCI panels, respectively. PD-L1, LAG-3, and CD8 expression was assessed by IHC. Results None of the cases demonstrated deficient MMR (dMMR) or MSI. In total, 43/74 cases (58.1%) were PD-L1+, including 1 tumor PD-L1+, 25 tumor-infiltrating lymphocytes (TILs) PD-L1+, and 17 cases involving concurrence of tumor and TIL PD-L1+. The rate of TIL PD-L1+ was remarkably higher than that of tumor PD-L1+ (P<0.001). We identified 20 LAG-3+ cases (27.0%, 20/74), all of which were PD-L1+. Co-expression of PD-L1 and LAG-3 was noted in 46.5% (20/43) of the PD-L1+ population. In the LAG-3+ subtype (co-expression of PD-L1 and LAG-3), high correlation between TILs PD-L1+ and LAG-3+ was observed (P<0.01). A high frequency of CD8+ (98.6%, 73/74) was observed. Conclusion dMMR/MSI characteristics may not be a practical predictive marker for ICIs in TNBC. PD-L1+ is more common in TILs than in tumors. In the PD-L1+ population, approximately half of the cases showed LAG-3 co-expression. For patients with a poor response to PD-1(L1) mono ICI, dual blockade of PD-1(L1) and LAG-3 may be a viable option for the management of TNBC.